Pengaruh Sambaran Petir Terhadap Sistem Proteksi Pada Peralatan Telekomunikasi PT. Telkom Pekanbaru - Muhammad Ibrahim; Edy Ervianto; Firdaus Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The tower BTS (Base Transceiver Station) is a high tower that is susceptible to lightning strikes. If a BTS tower was struck by lightning directly, then it would occur a more currents that flows on the system derived from the lightning surges, the lightning surge will distributed to a those channels made of metallic material with system connected to a telecommunication equipment through bonding bar. To protect the power lines from damage due to overcurrent the resulting by lightning strikes, then install the cutting tool, namely voltage surge arresters, in this case arresters used are metal oxide arrester varistor (MOV). In this research conducted to determine the arrester surge current capacity of required on the power channel that is connected to the arresters on theequipment telekomunikasis by simulation Alternative Transient Electromagnetic transients Program-Program (ATP-EMTP).Keywords : tower BTS, surge current, arrester MOV, ATP-EMTP